The History of the Portuguese Aviation - A Summary - Neves, Fernando M. S. P. (2022)
This article is intended as a summary of a new area of study on the History of the Portuguese Aeronautics and Aerospace and addresses issues such as: the forthcoming of the aircraft at Portugal, its military and civilian use; the scope of early days concerning Portuguese intercontinental flights and their authors; the development of air navigation devices by Portuguese inventors in the 1920s and 30s; the Aeronautics industry and the need to develop expertise in Aeronautical/Aerospace Engineering in Portugal during the centuries XX and XXI.